Appraiser of roadsid carpentry workshop in Iwo, Osun state, Nigeira (2012)
Cardiovascular disease has been recognized as the world’s leading cause of death and disability accounting for about 40% of all human mortality. Cardiac arrhythmia is a name for a large family of cardiac behavior that shows abnormalities in the electrical behavior of the heart. Cardiac action potential depicts the electrical wave propagation within the heart. This work presented the mathematical modeling of the action potential within the human cardiovascular system. The electrical activity of the heart is best mathematically modeled by coupled systems of differentials equations consisting of ordinary differential equations(ODEs) and partial differential equations (PDEs), mainly reaction-diffusion types. These equations are non-linear and present themselves as stiff problem, hence, difficult to solve numerically. More so, whole heart simulation using these models is a challenging scientific computing problem due the complex geometry and small scale details of human heart. In this work, the bidomain model was adopted for the modeling due to its ability to reflect the actual wave propagation in the cardiac tissue. The bidomain model was coupled with FitzHugh-Nagumo’s ionic model and then discretized in time using the explicit forward Euler method. A 2-D Java-based computer program was developed to simulate the adopted model. The generated wave was compared with the theoretical standard. The obtained results are very useful in that they provided valuable information on cardiac arrhythmias